Embryonal Sarcoma of the Liver in an Adult Patient. (29th May 2012) - Lightfoot, Nicole; Nikfarjam, Mehrdad
Abstract : Undifferentiated embryonal sarcomas (UESs) are uncommon tumours that are seen predominantly in late childhood. Cases in adults are rare and generally present once a large mass develops and may be mistaken for other tumours. A case of an UES of the liver with an isolated peritoneal metastasis is described. The patient presented with a palpable mass with imaging findings suggestive of a cystic tumour. She had complete surgical resection of the liver mass and isolated peritoneal metastasis. She was tumour-free on imaging at 6 months without adjuvant chemotherapy. An UES should be considered in the differential of large cystic hepatic lesions, with aggressive surgical resection considered when possible.